Meanings attributed to fatherhood by adolescents - Karla Jimena Araújo de Jesus Sampaio; Wilza Vieira Villela; Eleonora Menicucci de Oliveira (Escola Paulista de Enfermagem, Universidade Federal de São Paulo, 2014)
OBJECTIVE: To understand how adolescents perceive the experience and what meanings they attribute to fatherhood.METHODS: Research of a qualitative method, using interviews of 25 young people who had become fathers for the first time. Data were collected through semi-structured interviews, taped and transcribed in their entirety. Data analysis occurred using an initial and then an exhaustive reading of the material, synthesis of the results obtained, and identification of implicit content.RESULTS: The analysis and interpretation of this material allowed us to identify three thematic categories: the role of the young father; gains and losses with fatherhood, and solutions adopted during the experienced difficulties. It was evident that the exercise of fatherhood contributed to the assumption of masculinity, to play the role of guardian of the home and provider for the family.CONCLUSION: Fatherhood was seen as a positive experience that transformed teenagers into adults.